Functional Connectivity Abnormalities of Brain Regions With Structural Deficits in Primary Insomnia Patients - Xie, Dongdong; Qin, He; Dong, Fang; Wang, XianFu; Liu, Chang; Xue, Ting; Hao, Yifu; Liu, Bo; Yuan, Kai; Yu, Dahua (Frontiers in Neuroscience, 2020)
Objectives: To examine the abnormal resting state functional connections (RSFC) in structural deficits brain regions of primary insomnia (PI) patients. Methods: Thirty-three PI patients and 38 well-matched healthy controls participated in our study. We used voxel-based morphometry (VBM) and RSFC to study the functional connectivity abnormalities of brain regions with structural deficits in PI patients. Results: PI patients showed decreased gray matter (GM) volume in the left dorsolateral prefrontal cortex (DLPFC), left orbitofrontal cortex (OFC), bilateral middle frontal gyrus (MFC), right inferior frontal gyrus (IFG) and left inferior temporal gyrus. GM volume in the right MFC had a negative correlation with Self-Rating Scale of Sleep (SRSS) score and GM volume in the right IFG had a negative correlation with Insomnia Severity Index (ISI) score. Therefore, the right MFC and right IFG were selected as regions of interest (ROIs) for RSFC analysis. Compared with the healthy controls, we found PI patients had weakened RSFC between the right inferior parietal gyrus (IPC) and the right MFC and between the left OFC and right IFG. The RSFC between the right MFC and right IPC was negatively correlated with SRSS scores. The RSFC between the right IFG and left OFC was negatively correlated with ISI scores. Conclusions: In present study, we found structural changes in the right MFC and right IFG accompanied by RSFC changes. This finding may provide novel insights into the neural mechanisms of PI by combining structural and functional modality information.